PEMBERDAYAAN MASYARAKAT PESISIR MELALUI HILIRISASI RUMPUT LAUT MENJADI PANGAN FUNGSIONAL DAN ENERGI HIJAU BERBASIS TEKNOLOGI TEPAT GUNA SOLAR TECH DRYER - Rostini Rostini; Mardia Mardia; Andi Atrianingsih; Nur Aselda; Muh. Ikbal; Satriani Satriani (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Empowering coastal communities still faces challenges in increasing the added value of seaweed through downstream processing into functional foods and green energy. This study aims to evaluate the implementation of the Solar Tech Dryer, an appropriate technology, to improve drying efficiency, product quality, and the energy potential of processing residues. The method used was community service with a qualitative, participatory approach, including outreach, training, and production monitoring. The results show an increase in drying efficiency of approximately 40%, the product's bioactive quality remains high, and processing residues have the potential to generate green energy. These findings have implications for the economic empowerment of coastal communities, commodity downstreaming strategies, and the development of sustainable appropriate technology.